Country human development indicators: Caribbean profiles....-[19 ]- (UNDP GeorgetownGY)
Contains indicator tables for 16 Caribbean countries. Provides information ranging from education and health profiles, and demographic and natural-resource patterns to employment, food security and financial resource flows.
Documentation Centre has : 1994